Silent aspiration in patients with exacerbation of COPD. Issue 2 (23rd June 2016) - Zheng, Zeguang; Wu, Zhida; Liu, Ni; Chen, Ping; Hou, Peng; Wang, Xinni; Fu, Yimin; Liang, Weijian; Chen, Rongchang
Patients with chronic obstructive pulmonary disease (COPD) are susceptible to aspiration, probably due to discoordination between breathing and swallowing, cricopharyngeal muscle dysfunction, and changes in lung volume [1, 2]. Terada et al . [3] found a significantly higher prevalence of an abnormal swallowing reflex in patients with COPD than in healthy controls. Shaker et al . [4] found that patients with acute exacerbation of COPD (AECOPD) have a higher risk of aspiration. In this cross-sectional study, using the technetium-99m–sulfur colloid ( 99m Tc-SC) salivary scintigraphy method that is believed to be more sensitive than techniques using in previous studies, the prevalence and risk factors of silent aspiration in hospitalised AECOPD patients was studied. Radionuclide imaging of silent aspiration http://ow.ly/s3pz300hiSN